Representações cognitivas e cartográficas: algumas proposições metodológicas - Colette Cauvin (Confins)
In order to clearly understand the cognitive representations of the urban space, this paper presents an approach in three steps: identification, which highlights the importance of a place; its location more or less exact which indicates the level of the individuals’spatial knowledge, and the description which specifies the significant attributes of these places for the interviewed individuals. In order to obtain comparable maps, a precise protocol is proposed for each step.